Artificial disc replacement combined with fusion versus two-level fusion in cervical two-level disc disease - Shin, Dong Ah; Yi, Seong; Yoon, Do Heum; Kim, Keung Nyun; Shin, Hyun Cheol (Spine (Philadelphia, Pa. 1976), 2009)
A prospective analysis. The purpose of this study was to compare the clinical and radiologic outcomes of cervical artificial disc replacement (C-ADR) combined with anterior cervical discectomy and fusion (ACDF) and 2-level ACDF in patients with 2-level cervical disc disease. Adjacent segment degeneration is a long-term complication of ACDF, and estimated to affect 25% of patients within 10 years of the initial surgery. Two-level fusion leads to a substantially greater increase in intradiscal pressure than one-level fusion. It has been demonstrated that C-ADR maintains motion at the level of the surgical procedure and decreases strain on the adjacent segments for prevention of adjacent segment degeneration. In the case of 2-level cervical disc disease, hybrid surgery (HS), consisting of C-ADR combined with ACDF, may be a reasonable alternative to 2-level ACDF (2-ACDF). Between 2004 and 2006, 40 patients undergoing 2-level cervical disc surgery at our hospital were identified who met the following surgical indications: 2 consecutive level degenerative disc disease between C3/4 and C6/7; either a radiculopathy or myelopathy; and no response to conservative treatment for >6 weeks. Twenty patients of the HS group were matched to 20 patients of the 2-ACDF group based on age and gender. Patients were asked to check the neck disability index (NDI) and grade their pain intensity before surgery and at routine postoperative intervals of 1, 3, 6, 12, and 24 months. Dynamic flexion and extension lateral cervical radiographs were obtained in the standing position before surgery and at routine postoperative intervals of 1, 3, 6, 12, and 24 months. The angular range of motion (ROM) for C2-C7 and adjacent segments were measured using the Cobb method with PACS software. The HS group had better NDI recovery 1 and 2 years after surgery (P < 0.05). Postoperative neck pain was less in the HS group 1 month and 1 year after surgery (P < 0.05). There was no difference in arm pain relief between the groups. The HS group showed faster C2-C7 ROM recovery. The mean C2-C7 ROM of the HS group recovered to that of the preoperative value, but that of the 2-ACDF group did not (P < 0.05). The inferior adjacent segment ROM showed significant differences between the groups 6 and 9 months, and 1 and 2 years after surgery (P < 0.05, P < 0.01, P < 0.05, and P < 0.05, respectively). HS is superior to 2-ACDF in terms of better NDI recovery, less postoperative neck pain, faster C2-C7 ROM recovery, and less adjacent ROM increase.